PROSES PENGHUNIAN KAMPUNG PRINGGONDANI - Ikhwanuddin, Ikhwanuddin (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This research aims to reveal how the forming process of Pringgondani kampong, Catur Tunggal, Depok, Sleman, Jogjakarta province. The Pringgondani kampong is a densely populated kampong in the Gajah Wong’s river bank that can be categorize as an urban viilage or city’s kampong. The forming process of this area is attractive object to be researched, because of the status of this land as tanah kas desa (the property of village administration) borrowed as the rights of rented farming land. In other side, this research aims to explore the driven factors that influencing the inhabitation process that forming this settlement. The fenomenological method was used as method of research. This methods require unseperation between researcher and object of research. The object of research is observed without separation of it context. The information had been collected from the trusted informan then it was conformed to user or responder. The trusted informan are old people or the people who settle in this kampong erlier so their knowledge about kampong are assumed much more then the others. Trusted informan and responder is elected by purposive manner. The instruments of research are log book, pen, survey map and researcher. This research reveal the process of settlement in this Pringgondani kampong that can be seen by two sight: the first as a process of exchange of rented land right and the second as a process of attending of inhabitant. The factors influencing process of inhabitation are: status of land, unproductive land condition, recognition of village administration about this functional area as settlement, demand of rented room, and self-improvement of inhabitant. Keywords: process of inhabitation, rented land right, urban village